Financial Transparency as a Strengthening Effect of Corporate Social Responsibility Disclosure on Corporate Financing Constraints in the Context of Digital Transformation - Fauzi; Shabila Fitri Aulia; Rahmi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
In the digital transformation era, companies face increasing challenges in securing external financing amid growing demands for sustainable and accountable business practices. Corporate social responsibility (CSR) disclosure is expected to enhance stakeholder confidence and potentially reduce corporate financing constraints; however, its effectiveness may depend on the transparency of firms’ financial information. This study examines the effect of CSR disclosure on corporate financing constraints and evaluates the moderating role of financial transparency. The study used panel data from manufacturing companies listed on the Indonesia Stock Exchange, with the sample selected through purposive sampling. The final sample comprised 17 companies and 68 firm-year observations. Data were analyzed using panel data regression with EViews. The findings indicate that CSR disclosure has no significant effect on corporate financing constraints in the digital transformation era. Financial transparency also does not significantly moderate the relationship between CSR disclosure and corporate financing constraints, suggesting that it neither strengthens nor weakens the influence of CSR disclosure on firms’ access to funding. These results demonstrate that CSR disclosure alone may be insufficient to reduce financing constraints or improve corporate access to external capital. The study contributes to the literature by clarifying the limited role of CSR disclosure and financial transparency in explaining financing constraints among Indonesian manufacturing companies. Practically, companies should place greater emphasis on the quality of financial information, financial performance stability, and substantive governance practices, rather than relying solely on social disclosure, to strengthen investor and creditor confidence in corporate financing decisions.